Corpus Papyrorum Judaicarum: Volume 5, The Early-Roman Period (30 BCE–117 CE) - Hacham, Noah; Ilan, Ṭal; Jacobs, Deborah; Pioṭrḳovsḳi, Meron M.; Szántó, Zsuzsanna (Corpus Papyrorum Judaicarum, 2022)
The period between the Roman take-over of Egypt (30 BCE) and the failure of the Jewish diaspora revolt (115–117 CE) witnessed the continual devaluation in the status of the Jews in Egypt, and culminated in the destruction of its Jewish community. This volume collects and presents all papyri, ostraca, amulets and inscriptions from this early Roman period connected to Jews and Judaism, published since 1957. It is a follow-up of the 1960 volume 2 of the Corpus Papyrorum Judaicarum. It includes over 80 documents in Greek, Demotic, and Hebrew, both documentary and literary. The expansion of the scope of documents, to include languages other than Greek and genres beyond the documentary, allows for a better understanding of the life of the Jews in Egypt. The documents published in this volume shed new light on aspects discussed previously: The Demotic papyri better explain the Jewish settlement in Edfu, new papyri reveal more about Jewish tax, about the Acta papyri, and about the developments of the Jewish revolt. The magical papyri help explain cultural developments in the Jewish community of Egypt. This volume is thus a major contribution to the study of the decline of the greatest diaspora Jewish community in antiquity